Simulation and Millennials -- the Perfect Storm - Erlam, GD; Smythe, L; Wright, V (Scientific Research Publishing (SCIRP), 2016)
Simulation in its various forms has developed extensively over the past 15 - 20 years for use in undergraduate nursing programs. The widespread integration of technology-based educational tools into nursing curricula is raising concerns that technology rather than sound philosophically-based pedagogy is informing nursing education. Some believe that educational soundness has been overtaken by a focus on technological prowess. The manikins used in this immersive classroom often breathe, blink, and even speak in response to lecturer-controlled commands. This research explores how Millennials as a generational cohort (18 - 30 years of age) interface with the teaching/learning platform of simulation. This action research study is unfolded in three distinct action cycles involving 161 undergraduate nursing students. Millennial characteristics of confidence, high achievement, team orientation, technology focus, feedback-saturated, and trophy-seeking traits make them especially adept in immersive simulation environment. If supported by appropriate philosophical underpinnings, simulation as a teaching/learning platform has the potential to become the preferred classroom for Millennial nursing students.
Keywords: Simulation; Undergraduate nursing; Millennials; Scaffold; Action research